Konsep Keluarga Sehat Perspektif Psikologi dan Islam - Musrifah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Based on the phenomenon of human life, many people experience complex life problems, from top to bottom. In essence, all humans have their own life problems depending on their level. Such as economics, politics, family, children, both internal and external. It all depends on the individual concerned. Such problems are as follows: increasing life needs, individualistic and selfish feelings, competition in life, unstable conditions. Of all these problems, the author focuses on research on household life problems, because the author sees that in household life there are many affairs, it turns out that these stories are not only in soap operas or films, but also occur in real life. Why can this happen? This study uses a qualitative literature research approach. The data used uses primary and secondary data, the analysis used uses content analysis. This is all due to several factors including; 1. Economic factors, 2). Sexuality, 3). Miscommunication, 4). Lack of mutual trust and openness in the family, 5). Children, 6). Shallow faith. With a psychological approach, families can better understand and communicate harmoniously and intelligently, and with an Islamic approach, the family atmosphere can better understand each other's duties according to Islamic teachings/Islamic law.